To simplify the expression \( \sqrt{50} \times \sqrt{45} \), we start by using the property of square roots that states \( \sqrt{a} \times \sqrt{b} = \sqrt{a \times b} \). Therefore, we can combine the square roots:
\[ \sqrt{50} \times \sqrt{45} = \sqrt{50 \times 45} \]
Next, we calculate \( 50 \times 45 \):
\[ 50 \times 45 = 2250 \]
Now we have:
\[ \sqrt{50 \times 45} = \sqrt{2250} \]
To simplify \( \sqrt{2250} \), we factor \( 2250 \) into its prime factors. First, we divide \( 2250 \) by \( 10 \):
\[ 2250 = 225 \times 10 \]
Next, we focus on simplifying \( 225 \):
\[ 225 = 15 \times 15 = 15^2 \]
Now we return to \( 10 \):
\[ 10 = 2 \times 5 \]
Thus, we can write the factorization of \( 2250 \):
\[ 2250 = 15^2 \times 2 \times 5 = 3^2 \times 5^2 \times 2 \]
This can be combined as follows:
\[ 2250 = 2 \times 3^2 \times 5^2 \]
Now we apply the square root:
\[ \sqrt{2250} = \sqrt{2 \times 3^2 \times 5^2} = \sqrt{2} \times \sqrt{3^2} \times \sqrt{5^2} \]
Knowing that \( \sqrt{3^2} = 3 \) and \( \sqrt{5^2} = 5 \), we have:
\[ \sqrt{2250} = \sqrt{2} \times 3 \times 5 = 15 \sqrt{2} \]
Thus, the product of the original expression \( \sqrt{50} \times \sqrt{45} \) in simplest radical form is:
\[ \boxed{15\sqrt{2}} \]